2010
DOI: 10.4093/kdj.2010.34.5.294
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density in Prediabetic Men

Abstract: BackgroundThere are many studies regarding the effects of insulin on bone metabolism and changes in bone mineral density (BMD) in the setting of diabetes. The effect of prediabetes on BMD is not known.MethodsA total of 802 men participated in the Korea Rural Genomic Cohort Study (in Geumsan County). According to the results of an oral glucose tolerance test, subjects were classified into normal, prediabetic, and diabetic categories. One hundred twenty-four subjects diagnosed with type 2 diabetes were excluded,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 26 publications
3
15
0
1
Order By: Relevance
“…Additionally, in this study, QUS parameters and the T-score positively correlated with BMI and WHR. Similar findings were reported in other studies, as QUS parameters were inversely correlated with age and positively correlated with weight and BMI; however, no correlation was found with height [ 92 , 93 ].…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, in this study, QUS parameters and the T-score positively correlated with BMI and WHR. Similar findings were reported in other studies, as QUS parameters were inversely correlated with age and positively correlated with weight and BMI; however, no correlation was found with height [ 92 , 93 ].…”
Section: Discussionsupporting
confidence: 90%
“…This result is consistent with some previous studies. Firstly, Lee et al found no association between any prediabetes criteria and BMD in adult subjects (13). Another study in adolescent children with metabolic syndrome failed to show a relationship between glucose levels and BMD (18).…”
Section: Discussionmentioning
confidence: 98%
“…However, this conflict also exists among prediabetic patients. Whereas some studies report a positive association between prediabetes and bone mineral content or (BMC) (9,10), others suggest an inverse association (11,12) or no significant relationship (13). We aimed to investigate the relation between BMD and childhood obesity, and assess the effect of prediabetes on this relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Стоит отметить, что хроническое воспаление усиливает агрегацию β-амилоида, который в сочетании с нарушением инсулин-сигнальной трансдукции снижает транспорт и утилизацию глюкозы в головном мозге, активирует гликогенсинтаз-киназы 3 (GSK3), что увеличивает гиперфосфорилирование тау-белка, в конечном итоге, приводя к нейродегенерации [23]. В дополнение к этому, воспалительные цитокины, экспрессируемые в ответ на активность инфламмасом NLRP3, вносят решающий вклад в развитие резистентности к инсулину путем активации различных киназ, тем самым нарушая передачу сигналов инсулина [15].…”
Section: статистический анализunclassified